2022
DOI: 10.1021/acsomega.2c06234
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Adsorption of a Sulfonamide Antibiotic in Aqueous Solutions with N-doped Magnetic Biochar: Performance, Mechanism, and Reusability

Abstract: Conventional biochar has limited effectiveness in the adsorption of sulfonamide antibiotics, while modified biochar exhibits greater adsorption potential. Residues of sulfamethoxazole (SMX) in the aquatic environment can threaten the safety of microbial populations as well as humans. In this study, iron–nitrogen co-doped modified biochar (Fe-N-BC) was prepared from palm fibers and doped with Fe and urea via synthesis at 500 °C. Fe-N-BC has a richer surface functional group based on elemental content, X-ray pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Obviously, those results consistently demonstrated that the N-doping process significantly decreased the adsorption sphere of PBC but significantly increased the adsorption sphere of N-GBC. Similar results were also obtained in the study of Diao et al [39], which can be explained by the breaking down of carbon framework due to the gas produced by urea during pyrolysis [40].…”
Section: Modification Of Pore Structuresupporting
confidence: 88%
“…Obviously, those results consistently demonstrated that the N-doping process significantly decreased the adsorption sphere of PBC but significantly increased the adsorption sphere of N-GBC. Similar results were also obtained in the study of Diao et al [39], which can be explained by the breaking down of carbon framework due to the gas produced by urea during pyrolysis [40].…”
Section: Modification Of Pore Structuresupporting
confidence: 88%
“…All patterns display a strong D-band (∼1342 cm −1 ) and G-band (∼1595 cm −1 ), which generally represent the disorder or defects of the carbon structure and the graphitized structure, respectively. 27 The peak intensity ratio of the D band to G band ( I D / I G ) for 3.0PANI@AC900 (1.55) and 3.0PANI–AC900 (1.47) was higher than AC900 (1.03) and PANI900 (1.31), indicating that more defects were formed in the carbon structure due to the introduction of polyaniline precursors. 28 In particular, the maximum I D / I G value of 3.0PANI@AC900 demonstrates the lower degree of graphitization and the presence of more defects than 3.0PANI–AC900, which indicates that in situ nitrogen doping is better than physical blending nitrogen doping.…”
Section: Resultsmentioning
confidence: 95%
“…The nitrogen adsorption-desorption isotherm of the palm fronds, biochar, and MnO 2 /PF biochar is presented in Figure 4. This figure shows that the palm fronds and biochar possessed type II and IV isotherms with an H3 hysteresis loop [43], indicating the presence of macroporous and mesopores structures, while the MnO 2 /PF biochar adsorbent possessed a type IV isotherm with an H3 hysteresis loop, which is characteristic of a solid with a mesoporous structure [43]. On the other hand, the textural properties of the adsorbents are tabulated in Table 1.…”
Section: Bet Analysismentioning
confidence: 96%